Celso Garrido-Lecca y Hegel...un propósito desde la Wissenchaft der Logik - Alvarado, Boris (2026)
I would like to share a reflection that arises from the work of maestro Celso Garrido-Lecca on the centenary of his birth, and to compare it with Hegel, as if they were an absolute idea. Celso thinks of music as, and in, transformation and development. Hegel conceives the world of nature, history, and spirit as a process in constant movement and change, leaving in both cases the idea of the internal connection of that movement and its transformation.